FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN MEDIA FACEBOOK - Sopiah, Nyimas (JURNAL ILMIAH MATRIK, 2013)
Facebook is one of the social networking site that is very popular in Indonesia. Likewise with Bina Darma University students in particular faculties of Computer Science. Variable interest of students use facebook contained 4 variables, namely Information, Pleasure, Communications and Transactions. The fourth variable is the dependent variable. While independent variable is the attitude of students using Facebook. The purpose of this study was to determine the factors that influence student of Computer Science faculty in using Facebook and whether the interests of surfing usage has an influence on student attitude in using Facebook. Based on the analysis, the variables are based on the first sequence is Pleasure, Communication, Information and Transaction. Keywords: Facebook, Information, Pleasure, Communications, Transactions and Attitude